Profesionalitas Guru dan Tuntutan Orang Tua : Analisis Etis Atas Konflik Pendidikan di Sekolah - M. Hamzah Alfiansyah; Sintia Agustin; Rani Rani; Muhammad Padlilah; Arif Rahmat Triasa (Yayasan Literasi Sains Indonesia, 2026)
The shift in the educational paradigm towards a service industry model has transformed the parent-teacher relationship from a collaborative partnership into a transactional and tense dynamic, placing teachers in a dilemma between maintaining professional pedagogical authority and meeting parental demands. This qualitative study, employing a hermeneutic phenomenology approach, aims to reveal the essence of teachers' experiences in interpreting this conflict and to analyze it ethically. Data were collected through in-depth interviews with teachers, parents, and school principals, supplemented by document analysis, and interpreted through the lens of Paul Ricoeur. The findings, illustrated by a deep analysis of the case of corporal punishment at SMAN 1 Cimarga, reveal that the use of physical discipline represents a repressive Foucauldian power relation that objectifies the student's body. This approach only generates short-term, fear-based pseudo-obedience, fails to build critical consciousness, and instead teaches a hidden curriculum that legitimizes violence. Furthermore, such action contradicts humanistic educational philosophy and the national principle of Sistem Among. The discussion underscores a fundamental failure in educational dialectics and highlights the urgent need for a paradigm shift from punitive discipline to a restorative approach that repairs relationships and internalizes values. The study implies a critical necessity to redefine ethical boundaries and foster school-family collaboration to create a humane and integral educational ecosystem.